The Influence of TAM, Social influence, Security Relationship toward Intention to Use E Wallet through Attitude and Trust - Ulfa Khoirun Nisa; Nihayatu Aslamatis Solekah (Fakultas Ekonomi, UIN Maliki Malang, 2022)
The purpose of this study is to examine relationship of TAM, Social Influence and Security Toward Intention to use (IU) E-wallet with attitude and trust as intervening variables. The research uses quantitative approach with survey approach. The population of this survey is the people who live in Malang City with the conditions that they are 19-34 years old and the e-wallet used is (Gojek, OVO, Dana, LinkAja, Jenius). The samples taken was 150 respondents. The analysis technique used was SEM-PLS. The results showed that PU, SI, and S had no influence on IU e-wallets, only PEU had direct influence on IU e-wallets, Attitude could not mediate PU and PEU on IU e-wallet, but Trust could fully mediate Security against IU. This showed that the security of using the system can influence respondents' intention to use e-wallets based on trust in the system and it is recommended that e-wallet providers always pay attention to the security of their systems and simplify their applications so that users can benefit from using them.